Standardized ethanol extract of Tinospora crispa upregulates pro-inflammatory mediators release in LPS-primed U937 human macrophages through stimulation of MAPK, NF-κB and PI3K-Akt signaling networks - Md. Areeful Haque; Ibrahim Jantan; Hemavathy Harikrishnan; Waqas Ahmad (BMC, 2020)
Abstract Background Immunomodulatory effects of Tinospora crispa have been investigated due to its traditional use to treat several inflammatory disorders associated to the immune system. The present study reports the underlying mechanisms involved in the stimulation of 80% ethanol extract of T. crispa stems on pro-inflammatory mediators release in lipopolysaccharide (LPS)-primed U937 human macrophages via MyD88-dependent pathways. Methods Release of interleukin (IL)-1β and tumor necrosis factor (TNF)-α, and production of prostaglandin E2 (PGE2) were determined by using enzyme-linked immunosorbent assay (ELISA). Immunoblot technique was executed to determine the activation of MAPKs molecules, NF-κB, PI3K-Akt and cyclooxygenase-2 (COX-2) protein. Determination of pro-inflammatory cytokines and COX-2 relative gene expression levels was by performing the real-time quantitative reverse transcription polymerase chain reaction (qRT-PCR). A reversed-phase HPLC method was developed and validated to standardize the T. crispa extract and chemical profiling of its secondary metabolites was performed by LC-MS/MS. Results Qualitative and quantitative analyses of chromatographic data indicated that syringin and magnoflorine were found as the major components of the extract. T. crispa-treatment prompted activation of NF-κB by enhancing IKKα/β and NF-κB (p65) phosphorylation, and degradation of IκBα. The extract upregulated COX-2 protein expression, release of pro-inflammatory mediators and MAPKs (ERK, p38 and JNK) phosphorylation as well as Akt dose-dependently. T. crispa extract also upregulated the upstream signaling adaptor molecules, toll-like receptor 4 (TLR4) and MyD88. T. crispa-treatment also upregulated the pro-inflammatory markers mRNA expression. Conclusion The results suggested that T. crispa extract stimulated the MyD88-dependent signaling pathways by upregulating the various immune inflammatory related parameters.